2020
DOI: 10.11114/aef.v7i4.4910
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity and Efficiency of Vietnamese Securities Firms, 2009 to 2017

Abstract: This paper provides an examination of the impact of size, regulation and ownership structure on the productivity and efficiency of 53 securities firms in Vietnam in the years 2009 to 2017. The results show that the size of the firms and regulation has an impact on the performance of the firms. Foreign ownership also has a significant negative correlation with the firms’ efficiency, while majority ownership by domestic Vietnamese, individual shareholders (as opposed to ownership by institutional shareholders) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Smaller companies, lacking the capacity for technological innovation, experienced significant declines in both efficiency and productivity. Tran and Abbott (2020) studied how elements like size, regulations, and the structure of ownership affect the productivity and efficiency of 53 Vietnamese securities firms between 2009 and 2017. Their research showed that the size of securities companies and government rules have an impact on their functioning.…”
Section: Research Overview and Theoretical Foundationmentioning
confidence: 99%
“…Smaller companies, lacking the capacity for technological innovation, experienced significant declines in both efficiency and productivity. Tran and Abbott (2020) studied how elements like size, regulations, and the structure of ownership affect the productivity and efficiency of 53 Vietnamese securities firms between 2009 and 2017. Their research showed that the size of securities companies and government rules have an impact on their functioning.…”
Section: Research Overview and Theoretical Foundationmentioning
confidence: 99%